PENGARUH PEMBERIAN MOL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KANGKUNG DARAT (Ipomea reptans Poir) - Jumriani K, Jumriani K; Patang, Patang; Mustarin, Amirah (Universitas Negeri Makassar, 2017)
The aims of this research was to determine the effect of giving MOL toward growth, survival and production of kale. This research used a completely randomized design, which consists of 4 treatments and 3 replications consisted of A treatment (24%), B treatment (30%), C treatment (36%) and control. Parameters that was observed include growth, production and survival. Technique of data analyzed using analysis of variance. The results showed that the treatment of MOL concentration had an effect on the growth and production of kale. However, it no effect on the survival rate of kale. The best treatment has resulted from the addition of MOL concentration of 24% with characteristics plant height was 46.73 cm, the number of leaves was 45 strands on 28 days after planting, weight per plant was 14.67 g, and weight per polybag was 39,91 g after planting